LncRNA HULC Polymorphism Is Associated With Recurrent Spontaneous Abortion Susceptibility in the Southern Chinese Population - Fang, Zhenzhen; Yang, Yanfang; Xu, Yufen; Mai, Hanran; Zheng, Wanqi; Pi, Lei; Fu, Lanyan; Zhou, Huazhong; Tan, Yaqian; Che, Di; Gu, Xiaoqiong (Frontiers in Genetics, 2019)
Previous studies have revealed that genetic variation in genes that regulate cell migration might be associated with susceptibility to recurrent spontaneous abortion. HULC regulates the migration of a variety of cells, and genetic polymorphisms of HULC are associated with susceptibility to a variety of diseases, but their association with susceptibility to recurrent spontaneous abortion has not been reported. This study included 610 cases of recurrent spontaneous abortion and 817 normal controls, and the polymorphisms of the four SNPs were genotyped using the TaqMan method. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to assess the associations between selected SNPs and susceptibility to recurrent spontaneous abortion. Our results showed that three SNPs were significantly associated with a reduced risk of recurrent spontaneous abortion: rs1041279 (GG vs. GC/CC: adjusted OR = 0.745, 95% CI = 0.559-0.993, P = 0.0445), rs7770772 (GC/CC vs. GG: adjusted OR = 0.757, 95% CI = 0.606-0.946, P = 0.0143), and rs17144343 (AA/GA vs GG adjusted OR = 0.526, 95% CI = 0.366-0.755, P = 0.0005). Individuals with one to four genotypes showed a reduced risk of recurrent spontaneous abortion (adjusted OR = 0.749, 95% CI = 0.598-0.939). This cumulative effect on protection increased with increases in the observed number of genotypes (adjusted OR = 0.727 95% CI = 0.625-0.846, ptrend < 0.0001). Our study suggests that HULC might be a biomarker for risk for recurrent spontaneous abortion, but larger sample studies are needed to verify this result.